Pengaruh Antara Kepuasan Kerja Dan Insentif Terhadap Loyalitas Karyawan Di CV Bina Mandiri X - Maghfirotun Ajron Karimah; Budi Wahono; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The rapid development in the industrial world has resulted in fierce competition between business actors. One of these businesses is CV Bina Mandiri X. The purpose of this research with this type of explanatory research and quantitative approach is to find out and analyze the effect of job satisfaction and incentives on employee loyalty at CV Bina Mandiri X, either simultaneously or partially. The population in this study were all employees of CV Bina Mandiri X, totaling 60 employees. The sampling technique used is saturated sampling, where all members of the population are used as a sample which is then found to be 60 respondents. This research method uses multiple linear regression analysis with the SPSS analysis tool. Based on the results of this study, job satisfaction and incentives at CV Bina Mandiri X simultaneously and partially have an influence on employee loyalty. Keywords: Job Satisfaction, Incentives And Employee Loyalty